The Cost of Fear : The Welfare Effect of the Risk of Violence in Northern Uganda - Rockmore, Marc (World Bank, Washington, DC, 2016)
Although the effects of insecurity are believed to be important, these have never been directly measured. Previous estimates of the costs of conflict have only captured the joint effect of violence and insecurity. The distinction is important for understanding the origins of the costs and for policy design. Spatially disaggregated measures of insecurity are created based on the spatial-temporal variation in the placement of violence. These are used to generate the first estimates of the relative causal contributions of the risk and experience of violence. The article also provides the first micro-data based counterpart to the cross-country literature on the costs of conflict.